2018
DOI: 10.1016/j.jclepro.2018.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Cradle to grave environmental-economic analysis of tea life cycle in Iran

Abstract: Tea as the second most consumed none-alcoholic beverage in the world next to the water is involved with considerable environmental impacts during its life cycle. Because of the high importance of the tea sector in northern Iran, the present study aimed to assess the environmental burdens of tea in life cycle, including green tea leaf production in the farm and its transportation to the factory, tea processing, tea packaging, processed tea transportation to the local shop and its preparation in private househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 26 publications
0
17
1
2
Order By: Relevance
“…Soheili‐Fard et al . studied the environmental impacts of tea production system and they indicated that its environmental impacts could be mitigated by optimization of agro‐chemicals consumption such as chemical fertilizers. However, Iranian urea fertilizer production in 2012 was about 1,282,688 tons (Ministry of Jihad‐e‐Agriculture of Iran, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soheili‐Fard et al . studied the environmental impacts of tea production system and they indicated that its environmental impacts could be mitigated by optimization of agro‐chemicals consumption such as chemical fertilizers. However, Iranian urea fertilizer production in 2012 was about 1,282,688 tons (Ministry of Jihad‐e‐Agriculture of Iran, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported that the energy consumption of chemical fertilizer was the highest energy consumer during Iranian crop production in general [16,37,52,95-100]. Soheili-Fard et al [101] studied the environmental impacts of tea production system and they indicated that its environmental impacts could be mitigated by optimization of agro-chemicals consumption such as chemical fertilizers. However, Iranian urea fertilizer production in 2012 was about 1,282,688 tons [48] (Ministry of Jihad-e-Agriculture of Iran, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of inventory is the second stage of LCA, involving the computation of the amount of each output and input [14] . Based on the functional unit, this stage denotes a comprehensive collection of energy outputs, inputs, materials, along with the emissions to soil, air, and water in all steps of the system [15] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…While tea production is not a GHG-emission-intensive agricultural sector, the scale at which tea is grown and consumed makes it an important focus for GHG emissions reduction. Already a variety of studies have been undertaken examining the energy efficiency, carbon footprint and environmental-economic analysis of tea production in India [14,15], Iran [16][17][18], Sri Lanka [19,20], Malawi [21], Turkey [22] and Kenya [23]. Cichorowski et al [14], Doublet and Jungbluth [15], and Azapagic et al [23] used the life cycle assessment method to analyze the greenhouse gas emissions of tea cultivation and consumption.…”
Section: Introductionmentioning
confidence: 99%